2021
DOI: 10.1002/term.3173
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired hydrogel surfaces to augment corneal endothelial cell monolayer formation

Abstract: Corneal endothelial cells (CECs) have limited proliferation ability leading to corneal endothelium (CE) dysfunction and eventually vision loss when cell number decreases below a critical level. Although transplantation is the main treatment method, donor shortage problem is a major bottleneck. The transplantation of in vitro developed endothelial cells with desirable density is a promising idea. Designing cell substrates that mimic the native CE microenvironment is a substantial step to achieve this goal. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Both micro- (∼1 µm) and nano-sized (∼250 nm) pillars were found to facilitate the in vivo -like morphology of CEnCs, promote their proliferation with higher cell density and smaller cell size ( Muhammad et al, 2015 ; Rizwan et al, 2017 ), and enhance the expressions of Na + /K + ATPase and cell–cell tight junction protein Zonula Occludens-1 (ZO-1) ( Koo et al, 2014 ; Muhammad et al, 2015 ; Palchesko et al, 2015 ; Rizwan et al, 2017 ). Recently, a small patterned hydrogel surface with physiologically relevant hexagon densities (∼2000 hexagons/mm 2 ) and a similar elastic modulus to native Descemet’s membrane (∼50 kPa) was constructed and augmented the formation of monolayers with higher cell density ( Erkoc-Biradli et al, 2021 ). In addition, substrates with hexagonal microtopography can promote differentiation of human mesenchymal stem cells into corneal-endothelial-like cells ( Gutermuth et al, 2019 ).…”
Section: The Impact Of Mechanical Cues From the Extracellular Matrixmentioning
confidence: 99%
“…Both micro- (∼1 µm) and nano-sized (∼250 nm) pillars were found to facilitate the in vivo -like morphology of CEnCs, promote their proliferation with higher cell density and smaller cell size ( Muhammad et al, 2015 ; Rizwan et al, 2017 ), and enhance the expressions of Na + /K + ATPase and cell–cell tight junction protein Zonula Occludens-1 (ZO-1) ( Koo et al, 2014 ; Muhammad et al, 2015 ; Palchesko et al, 2015 ; Rizwan et al, 2017 ). Recently, a small patterned hydrogel surface with physiologically relevant hexagon densities (∼2000 hexagons/mm 2 ) and a similar elastic modulus to native Descemet’s membrane (∼50 kPa) was constructed and augmented the formation of monolayers with higher cell density ( Erkoc-Biradli et al, 2021 ). In addition, substrates with hexagonal microtopography can promote differentiation of human mesenchymal stem cells into corneal-endothelial-like cells ( Gutermuth et al, 2019 ).…”
Section: The Impact Of Mechanical Cues From the Extracellular Matrixmentioning
confidence: 99%
“…Furthermore, in our previous work, we prepared hexagonal wellpatterned polyacrylamide (PA) cell substrates via bioinspiration approach to enhance CEC proliferation. Substrates with physiologically relevant pattern density provided the most favorable cellular results in terms of cell density and cell proliferation [74]. In addition to abovementioned cell substrates, several substrate materials such as polyurethane, silicon surfaces, polycaprolactone, chitosan, polystyrene with various feature type and dimensions were studied for corneal stromal or epithelial cell types to examine the effect of topography [73].…”
Section: Discussionmentioning
confidence: 99%
“…There is an extensive list of bioengineered materials -whether biomaterials or synthetic polymers -that have been investigated for use as a scaffold [54][55][56][57]. These include amniotic membrane, decellularized tissue such as human DM, corneal stroma, lens capsule, porcine or bovine corneal posterior lamellae [58], silk fibroin, gelatin [59,60], hydrogel [61], collagen, chitosan, agarose and poly-e-lysine [55]. A study comparing four types of electrospun nanofibre scaffolds found that blended polycaprolactone (PCL)/ collagen and PCL/gelatine were associated with significantly higher CEC viability compared with PCL alone, and PCL/chitosan [62].…”
Section: Corneal Endothelial Cell Delivery and Adhesionmentioning
confidence: 99%